KONTRIBUSI PAJAK KENDARAAN BERMOTOR TERHADAP PENDAPATAN ASLI DAERAH (PAD) PROVINSI SULAWESI SELATAN (Studi Pada Kantor Dispenda Provinsi Sulawesi Selatan - Hasan Basry; Ahmad Akhyar Abdul Ahad (Universitas Negeri Makassar, 2018)
This study aims to determine: 1) Phase of the taxation of motor vehicles in the office Dispenda South Sulawesi Province, 2) Contribution of the motor vehicle tax on revenue of South Sulawesi province, 3) Obstacles encountered in the collection of motor vehicle tax in the office DISPENDA South Sulawesi Province. This research is a qualitative descriptive study. Research Location is in South Sulawesi Provincial Revenue Office. Where is the source of primary data obtained from informants. The informant made up 5 ie Head of Local Tax Revenue South Sulawesi Province, Head of Data Collection and Determination, Head of Planning, Officer Perceptions and Vehicle Owners. Sources of secondary data obtained from such data, data on the number of motor vehicles in South Sulawesi, target data and the realization of revenue from motor vehicle tax, target data and realization of provincial tax in South Sulawesi, and data Local Revenue South Sulawesi province where the data was obtained from 2013, 2014, and 2015. the data collection procedures used were interviews, observation, and documentation. While the analysis of the data used is descriptive analysis. The results showed that: 1) The stages in the implementation of tax collection vehicles starting with reporting or registration of the vehicle by the taxpayer, after it emerged with a clear and definite object and subject-based PKB SPPKB, then published SKPD. Furthermore, the payment of motor vehicle tax, which is paid at the same time paid in advance for 12 months. Billing is done by issuing letters of reprimand for taxpayers due and for taxpayers who do not immediately pay taxes subject to administrative sanctions and criminal sanctions. 2) During the period 2013, 2014 and 2015, the contribution to the PAD PKB South Sulawesi fluctuate, which in 2013 accounted for 28.23%, whereas in 2014 contributions fell to 26.69%, and in 2015 contributions rose to 27.74%. So that the authors can conclude that the average contribution of the PKB against revenue of 27.52% or Rp. 814,521,234,794.00. 3) The implementation of tax collection vehicle is not in spite of various obstacles, such as: (1) the completeness of the file taxpayer such as ID cards and reg, (2) the number of objects delinquent motor vehicle tax, (3) the improvement of the tax (4) ignorance of the community on places of payment of tax, (5) service is often complicated.